THE ROLE OF ARTIFICIAL INTELLIGENCE IN DEVELOPING NEW FORMS, METHODS, AND APPROACHES IN COMMUNICATIVE LANGUAGE TEACHING - Abdurahmonova Dilshoda Bohodirovna; Ziyadullayeva Iroda Ilxom qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In the context of modern education, communicative language teaching (CLT) is undergoing a new stage of development. This process is closely connected with the integration of artificial intelligence (AI) into the educational system. AI technologies provide new opportunities to improve the quality of language teaching by focusing on communication, interaction, and real-life language use. The use of AI-based tools allows teachers to create innovative forms, methods, and approaches in teaching, which contributes to the development of learners’ communicative competence. This article discusses the role of artificial intelligence in enhancing communicative language teaching and highlights its advantages, challenges, and pedagogical significance.